KONTRADIKSI ANTI TAKWIL âABDUL âAZÃZ BIN âABDULLÃH BIN BÃZ: TAFSIR TERHADAP ANTROPOMORPHISME - Mujahid, Ahmad (Jurnal Ilmu Ushuluddin, 2015)
In Qurâanic studies, the issues of Muhkam and Mutasyabbih verses always have been discussed, how to understandÂ each them. Interpreting mutasyabihat verses has been a need because many of them tell about theology in the context ofÂ anthropomorphism. Almost all scholars tend to use takwil to interpret them, but Abdul AzÃ®z bin AbdullÃ¢h bin BÃ¢zÂ offered the opposite method. He avoided takwil. In this study, this writing discusses how Ibn BÃ¢z understood mutasyabihatÂ verses especially about anthropomorphism. As a conclusion, the researcher found that the anti-takwil is stated by IbnÂ BÃ¢z and his allies, in its practice was sometimes contradictory. To enrich this article, the writer will trace the genealogyÂ of the thought of Ibn BÃ¢z and his dialectic with the understanding or other streams such as Muâtazilah, AsyâariyyahÂ to MaturidiyahÂ